The Analgesic Effect of Salvia reuterana: The Analgesic Effect of Salvia reuterana - Monsef Esfahani, Hamidreza; Amirshahrokhi, Keyvan; Mashmool, Atiyeh; Moridi Farimani, Mahdi; Dehpour, Ahmadreza; Miran, Mansour (Iranian Journal of Pharmaceutical Sciences, 2021)
Salvia reuterana, commonly known as Maryam Goli Esfahani, is a member of the Labiateae family. In Iranian folk medicine, aerial parts of S. reuterana have been used as sedative and anxiety. Evaluation of various extracts of the plant for their analgesic activity revealed that treatment of mice with n-hexane extract (500 mg/kg, i.p.) significantly increased the latency time as compared to the control group. Fractionation of the hexane extract of S. reuterana led to the isolation of sclareol as the main compound (0.19% w/w). Column chromatography was used to isolation of compounds from S. reuterana and a spectroscopic method including NMR was used to identification of the isolated compound. Evaluation of the analgesic effect of sclareol using a hot plate, tail-flick, and formalin tests in mice confirmed the potent analgesic effect of sclareol as an effective compound of S. reuterana. These results showed that the n-hexane extract of aerial parts of S. reuterana and its main constituent sclareol showed significant analgesic activity in different rodent nociceptive behavioral tests.